ANALISIS PENGGUNAAN BAHASA INDONESIA DI POLRESTABES MEDAN - Situmorang, Siska Dewi Titania (CULTURAL EDUCATION JOURNAL OF LITERATURE AND CULTURE, 2021)
This study aims to describe the form of politeness in the Indonesian language of the community towards the police on traffic checks of the Medan Police and to describe the form of politeness in the Indonesian language of the police towards the public at the traffic inspection of the Medan Police. This research is a qualitative research type, namely: (1) the data comes from natural police-observer team interactions, (2) the results of the study provide a description of the politeness data of the community to the police based on the symptoms or phenomena that are inductively researched, (2) 3) the researcher acts as the main instrument of data collection and data analysis, and (4) the data collected is in the form of words. The results of this study are that the use of Indonesian among the police is not as fluent as when using informal language. This is due to their lack of good and correct Indonesian in their daily life. Even within them an uneasiness arises when speaking standard Indonesian. Even though it is very natural that they as government employees can use their national language and show their identity as the Indonesian Nation.   The police as people who work for the government also use various technological devices to support work activities. The language of instruction in various technological devices is mostly English as an international language. In addition, several divisions in certain government agencies require mastery of English and other foreign languages according to their job duties